2015
DOI: 10.1007/s11255-015-0981-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma genistein and risk of prostate cancer in Chinese population

Abstract: ObjectivesGenistein is one of the main soy isoflavones in our daily diet. There were studies proving that high-dietary intake of genistein may relate to the low morbidity and mortality of prostate cancer (PCa) in the Asian population. Since there were few studies of plasma genistein level in the Chinese population, we performed this study to preliminarily evaluate the associations among plasma genistein, epidemiologic factors and PCa in a Chinese population.MethodsBetween 2012 and 2013, 100 men over the age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Of the 2531 articles that were screened by abstract, 39 articles were found to contain potentially relevant information and were evaluated by full text review. Upon reviewing the full text articles for the aforementioned inclusion criteria, 30 articles were included in the final analysis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Of these 30 articles, 24 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2531 articles that were screened by abstract, 39 articles were found to contain potentially relevant information and were evaluated by full text review. Upon reviewing the full text articles for the aforementioned inclusion criteria, 30 articles were included in the final analysis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Of these 30 articles, 24 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 articles included for analysis, fifteen [ 28 , 29 , 30 , 32 , 34 , 37 , 38 , 39 , 41 , 42 , 47 , 48 , 49 , 52 , 56 ] articles were case-control studies, eight [ 27 , 31 , 33 , 36 , 43 , 45 , 46 , 53 ] articles were cohort studies, and seven [ 35 , 40 , 44 , 50 , 51 , 54 , 55 ] articles were nested case-control studies (NCC). The total number of study participants included was 266,699, and the total number of PCa cases reported was 21,612.…”
Section: Resultsmentioning
confidence: 99%
“…Genistein (5,7,4′-trihydroxyisoflavone), a soybean-derived isoflavone, has been identified as a potential cause for the low incidence of certain types of tumors, including lung cancer [ 164 ], breast cancer [ 165 ], gastric cancer [ 166 ], colon cancer [ 167 ], HCC [ 168 ], and prostate cancers [ 169 ]. Genistein can exert its chemopreventive activities in each stage of multistep carcinogenesis through inhibiting tumor cell proliferation, inducing tumor cell differentiation, and triggering cell cycle arrest and apoptosis in some cell types [ 170 , 171 ].…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating epidemiological evidence has highlighted a geographical basis for PCa incidence, and isoflavone consumption may be related to this phenomenon. Indeed, PCa is more common in Western than Asian populations, and several trials have demonstrated that soy derivatives genistein and daidzein can prevent the development and progression of this tumor in Japanese and Chinese men [293][294][295][296]. On the contrary, the data collected in European patients are still contradictory.…”
Section: Clinical Impactmentioning
confidence: 99%